Impact of suspected preterm labour in foetal cardiovascular and metabolic programming: a prospective cohort study protocol - Abadía-Cuchí, Natalia; Clavero-Adell, Marcos; González, Jesús; Medel-Martinez, Ana; Fabre, Marta; Ayerza-Casas, Ariadna; Youssef, Lina; Lerma-Irureta, Juan; Maestro-Quibus, Pilar; Rodriguez-Calvo, Jesús; Ruiz-Martinez, Sara; Lerma, Diego; et al. (BMJ open, 2024)
IntroductionSuspected preterm labour (SPL) is an obstetric complication that occurs in 9% of all pregnancies and is the leading cause of antenatal hospital admissions. More than half of women with SPL deliver a premature baby which is a known risk factor for developing cardiovascular and metabolic disorders in childhood and later in adult life. On the other hand, the other half of these women will deliver at term, labelled as ‘false preterm labour’. Although this has been thought to be a benign condition, accumulating evidence reported in recent years showed long-term effects for the foetus, neonate and infant even when birth occurs at term. However, the impact of SPL on cardiovascular and metabolic programming has not been studied yet. The aim of this prospective cohort study is to evaluate the impact of SPL on cardiac remodelling and function and on cardiovascular and metabolic profiles independently of gestational age at birth.Methods and analysisProspective cohort study of subjects exposed and not exposed to an episode of SPL. Women with singleton pregnancies who are admitted at a tertiary hospital due to SPL and matched controls will be recruited. Evaluation of cardiovascular remodelling by foetal echocardiography will be performed during admission. Cord blood will be collected at birth in order to analyse different metabolomic footprints and several cardiovascular and metabolic risk biomarkers. Moreover, children will undergo an echocardiography 6 months after birth. The relationship between SPL and cardiovascular and metabolic programming will be modelled considering different covariates such as socioeconomic factors, perinatal characteristics, lifestyle, diet and exercise.Ethics and disseminationEthical approval was granted in April 2020 from CEIC Aragón (CEICA) (C.P.-C.I. PI20/136). Study outcomes will be disseminated at international conferences and published in peer-reviewed scientific journals.Trial registration numberNCT05670665.